OPRESI DAN PERUBAHAN RELASI KUASA ANTARA TOKOH SI PEREMPUAN DAN BADRAN BADAWI DALAM CERITA PENDEK THE ANSWER IS NO KARYA NAGUIB MAHFOUZ - Heri Dwi Santoso (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2014)
Not only in plays and novels but in short stories and even poems, feminist voices can be conveyed so massively. In line with that, this study on the short story The AnswerIs No aims to unveil the feminist voice in the story. Feminist approach, particularly focusing on some concepts in feminism, such as sexual oppression, binary opposition and relation of power in the patriarchal paradigm are used to analyze thework. The result of the study shows that sexual oppressions done to the character Her, the protagonist, in the story cause her more and more aware of the relation of power between her and the oppression. It causes the gradual changes of the relation of power between her and the oppressor, strongly indicated at the end with her denial to marry.Keywords: sexual oppression, relation of power, denial to marry.